Safety Challenges in Battery Swapping Operations of Electric Underground Mining Trucks - Alberto Martinetti; Ognjen Popović; Micaela Demichela; Pier Paolo Oreste; Aleksandar Cvjetić; Vladimir Milisavljević (Applied Sciences, 2025)
Recently, the global landscape of public transportation has witnessed a transformative shift towards sustainable and efficient modes of mobility, with particular emphasis on electric vehicles (EVs) and their integration into industrial applications. The mining industry, including the underground mining of the mineral resources sector is following this trend. However, underground mines are critical environments and the adoption of EVs needs to be carefully analysed. This study investigates the associated hazards and risks of adopting EVs (such as dumpers and loaders) focusing on the swapping battery operations. First, current hazards related to battery swapping are identified—21 in total, occurring in 25 instances. After, risks are assessed and associated with specific hazards. Finally, possible measures and solutions for reducing the impacts of these risks on the performance of the EVs are offered.